KEPUASAN PELANGGAN PADA BANK ISLAM STUDI KASUS SUATU BANK ISLAM DI INDONESIA - Sofyan S Harahap; Muhammad Nur Nasution; Ramlan Harahap (Media Riset Bisnis & Manajemen, 2006)
"Even Egypt, Malaysia, Pakistan and other countries have established and experienced in Islamic bank earlier than of Indonesia, history and development of Islamic bank in Indonesia is unique and spectacular. Even Indonesia is the most populous Muslim country the first Islamic bank was established in 1992 under strong support of Presiden Soeharto. Then other two banks were established (Bank Syariah Mandiri in 1999 and Bank Syariah Mega Indonesia 2004. Bank Indonesia as the indonesia's central bank has opended the door to conventional bank to open their syariah unit Islamic banks among others: BRI, BNI, BII, Danamon, IFI, Permata, Bukopin, BTN, Niaga, bank DKI dan bank Jabar. Market share of Islamic bank in Indonesia in 2006 was 1,52 %. The paper stuies how An Islamic bank provide service and what the perception of customers on 7 dimensions of service quality: "voluntere, employee competence, security, retiability, emphaly, responsiveness and tangible. Using survey method and field study the study shows that satisfactory was in bank information, service employees, syariah implementation, emphaty and responsiveness. Customers put high expectation on implimentation of syariah, reliability, product variations e.g ATM, deposits, educational deposit, Islamic card, employee's knowledge on bank products, service and uniform.